2017
DOI: 10.5334/gjgl.92
|View full text |Cite
|
Sign up to set email alerts
|

On the pseudo-small clause construction in Japanese: New evidence for A-movement out of a CP and its theoretical implications

Abstract: This paper provides new evidence for the availability A-movement out of a CP and considers its theoretical implications. The discussion concerns what I call the "pseudo"-small clause construction in Japanese, which has not received much attention in the literature. The pseudo-small clause construction shows a puzzling constraint on major subjects originating in complement clauses: the major subjects must receive accusative Case from a matrix predicate despite the availability of nominative Case within the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…When the ECMed subject remains within the ReportP complement, the former must receive accusative Case via Agree (however, see Taguchi 2015, Abe 2016). Given that two major arguments for the optional‐raising analysis and Agree have been called into question in this article, which has shown that the relevant phenomena can be reanalyzed without assuming the optionality of raising or Agree, it is worth considering if Agree is in fact operative for Case licensing in Japanese (for discussion, see Fukui 1986, Kuroda 1988, Hiraiwa 2001, 2005, Nomura 2005, Ura 2007, Saito 2016, M. Takahashi 2011, Kitahara 2017, M. Takahashi 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When the ECMed subject remains within the ReportP complement, the former must receive accusative Case via Agree (however, see Taguchi 2015, Abe 2016). Given that two major arguments for the optional‐raising analysis and Agree have been called into question in this article, which has shown that the relevant phenomena can be reanalyzed without assuming the optionality of raising or Agree, it is worth considering if Agree is in fact operative for Case licensing in Japanese (for discussion, see Fukui 1986, Kuroda 1988, Hiraiwa 2001, 2005, Nomura 2005, Ura 2007, Saito 2016, M. Takahashi 2011, Kitahara 2017, M. Takahashi 2017).…”
Section: Discussionmentioning
confidence: 99%